10th AIAA/CEAS Aeroacoustics Conference 2004
DOI: 10.2514/6.2004-2817
|View full text |Cite
|
Sign up to set email alerts
|

Time-Linearized Time-Harmonic 3-D Navier-Stokes Shock-Capturing Schemes

Abstract: In the present paper, a numerical method for the computation of time‐harmonic flows, using the time‐linearized compressible Reynolds‐averaged Navier–Stokes equations is developed and validated. The method is based on the linearization of the discretized nonlinear equations. The convective fluxes are discretized using an O(Δx H3) MUSCL scheme with van Leer flux‐vector‐splitting. Unsteady perturbations of the turbulent stresses are linearized using a frozen‐turbulence‐Reynolds‐number hypothesis, to approximate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…This paper being oriented towards forced response prediction, forcing function estimation techniques are presented here. For the aeroelastic stability determination, the reader can refer to [4], [5] and [12]. It can be mentioned that the total damping of the structure must be known for the forced response analysis.…”
Section: Cfd Toolsmentioning
confidence: 99%
“…This paper being oriented towards forced response prediction, forcing function estimation techniques are presented here. For the aeroelastic stability determination, the reader can refer to [4], [5] and [12]. It can be mentioned that the total damping of the structure must be known for the forced response analysis.…”
Section: Cfd Toolsmentioning
confidence: 99%
“…There are mainly two different approaches for the computation of time-periodic unsteady flows in turbomachinery (He 2010), the time-marching methods (Erdos et al 1977), which time-integrate the flow equations, and the nonlinear harmonic (Chen et al 2001;He 2008;McMullen, Jameson, and Alonso 2006) and harmonic-balance (Hall et al 2002;Hall 2007, 2008) methods, which solve a coupled set of timeindependent problems to determine the Fourier coefficients of the decomposition of the flow into harmonics, eventually with multiple fundamental frequencies (He 1992;Li and He 2002;Ekici and Hall 2008). The introduction of nonlinearity, through coupling between the equations for various harmonics (Hall et al 2002), is essential to resolve the instability problems observed in the fully linearised harmonic approaches Giles 2003, 2004;Agarwal, Morris, and Mani 2004;Chassaing and Gerolymos 2008), by nonlinear saturation of the amplitude of instabilities, as shown in He (2008), who analyses the nonlinear harmonic method Ning and He 1998).…”
Section: Introductionmentioning
confidence: 98%
“…The comparison of performance between the time-marching and the harmonic approaches depends on the particular computational case. If the multiharmonic content of the flow is small, so that only a few harmonics are required, the computational gain by use of harmonic methods is high, especially for low reduced frequencies (Chassaing and Gerolymos 2008). On the other hand, when multiharmonic content of the flow is important and reduced frequencies are high, well-tuned dual-time-stepping time-marching methods (Chassaing, Gerolymos, and Vallet 2003b) become quite competitive (Haugeard 1996).…”
Section: Introductionmentioning
confidence: 99%